Effects of the corporate wellness program on nutritional status parameters in employees with obesity - Sugiarto Sugiarto; Mohammad Arif Ali; Etika Ratna Noer; Yuliana Noor Setiawati Ulvie; Andi Kurniawan; Mutiara Amalia Fadzilla Raharjo; Ani Mazlina Dewi Mohamed; Setya Rahayu; Azkia Agustina; Gustiana Mega Anggita; Zahrah Zakiya Ahda (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2026)
ABSTRACTBackground: The Corporate Wellness Program (CWP) is a new physical exercise initiative designed to address the rising prevalence of obesity among PERTAMINA employees. Obesity negatively affects work performance. Body mass index (BMI) alone is not a sufficient indicator of obesity; therefore, additional measures such as visceral fat assessment are needed. Although nutritional interventions and physical activity are effective in reducing obesity, the effectiveness of structured workplace exercise programs requires further investigation using comprehensive parameters.Objective: the purpose of the study was to investigate effects of the CWP on body weight, BMI, and visceral fat in obese employees.Materials and Methods: A quasi-experimental one-group pre-test and post-test design was used. Ethical approval was obtained from the Institutional Ethics Committee. Twenty-six participants were selected from 150 employees using purposive sampling. The CWP was developed based on the FITT (Frequency, Intensity, Time, and Type) principle, with progressive overload applied throughout the intervention. Participants completed 24 exercise sessions (60 minutes per session, three times per week) equal to 2 months of intervention. Body weight, height, and visceral fat were measured using the Tanita BC-545N segmental body composition scale and the Tanita HR-200 wall-mounted height rod, following standardized procedures. A paired-sample t-test was used to compare pre- and post-intervention outcomes.Results: Participants showed a meaningful decrease in body weight, females dropping from 85.73 kg to 78.63 kg (−7.10 kg), males from 97.75 kg to 91.27 kg (−6.48 kg). BMI followed the same downward trend, females falling from 33.05 kg/m² to 30.55 kg/m² (−2.51 kg/m²), and males from 34.15 kg/m² to 31.92 kg/m² (−2.23 kg/m²) as p < 0.05. Visceral fat levels were also significantly reduced, females from 11.07 % to 10.00 % (−1.07 %), and males from 16.97 % to 15.11 % (−1.87 %) as p < 0.05).Conclusion: The CWP effectively contributed to reductions in obesity indicators among PERTAMINA employees.Keywords : Body mass index; body weight; fitness and health; physical exercise; visceral fat